Microfluidic-based functional materials: new prospects for wound healing and beyond. Issue 41 (12th October 2022) - Zhao, Wenbin; Zhang, Yage; Liu, Lijun; Gao, Yang; Sun, Wentao; Sun, Yong; Ma, Qingming
Abstract : Microfluidics has been applied to fabricate high-performance functional materials contributing to all physiological stages of wound healing. The advances of microfluidic-based functional materials for wound healing have been summarized. Abstract : As a popular clinical research topic, the use of functional materials to promote wound healing has attracted significant attention. Microfluidics has been demonstrated as one of the most promising and versatile technologies to fabricate high-performance functional materials contributing to all physiological stages of wound healing. In this respect, we review the state-of-the-art advances in the development of microfluidics for functional material preparation with key applications in wound healing. We first elaborate on the physiological principle of wound healing and the fundamentals of microfluidics. Then we categorize and depict a variety of microfluidic approaches to fabricate functional materials with well-tailored internal structures and integrated functions for wound treatment. We also summarize recent representative microfluidic-based functional materials to facilitate different stages of wound healing. This review concludes with our perspectives on the future directions and challenges in microfluidic investigation of functional wound healing materials, with an emphasize on its versatility in the clinic.